Enhancing Enzymatic Digestibility of Coconut Husk using Nitrogen-assisted Subcritical Water for Sugar Production - Maktum Muharja; Nur Fadhilah; Tantular Nurtono; Arief Widjaja (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Coconut husk (CCH) as an abundant agricultural waste in Indonesia has the potential to be utilized for sugar production, which is the intermediate product of biofuel. In this study, subcritical water (SCW) assisted by nitrogen (N2) was developed to enhance the enzymatic hydrolysis of CCH. SCW process was optimized by varying the operation condition: the pressure of 60-100 bar, the temperature of 150-190 °C, and the time of 20-60 min. The SCW-treated solid was subsequently hydrolyzed by utilizing a mixture of commercial cellulase and xylanase enzymes. The result shows that the optimum total sugar yield was obtained under the mild condition of SCW treatment, resulting in the sugar of 15.67 % and 10.31 % gained after SCW and enzymatic hydrolysis process, respectively. SEM and FTIR analysis of SCW-treated solid exhibited the deformation of lignin and solubilization of cellulose and hemicellulose, while XRD and TGA revealed an increase of the amount of crystalline part in the solid residue. The use of N2 in SCW treatment combined with enzymatic hydrolysis in this study suggested that the method can be considered economically for biofuel production from CCH waste in commercial scale. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).